Polymer microbubbles as universal platform to accelerate polymer mechanochemistry - Jilin Fan; Regina Lennarz; Kuan Zhang; Ahmed Mourran; Jan Meisner; Mingjun Xuan; Robert Göstl; Andreas Herrmann (Nature Communications)
Abstract The flow-induced activation of mechanophores embedded in linear polymers by ultrasound (US) suffers from slow mechanochemical conversions at the commonly used frequency of 20 kHz and in many cases remains ineffective with higher MHz frequencies. Here, we present polymeric microbubbles (PMBs) as a platform that accelerates the mechanochemical activation of several mechanophores under both 20 kHz and MHz irradiation. MHz irradiation generated by biocompatible high-intensity focused US (HIFU). Through their pressure-sensitive gas core, PMBs act as acousto-mechanical transducers for the transformation of sound energy into stretching and compression forces as well as fracturing the polymer shell by the volume oscillation of PMB. We investigate three different mechanophores among which one flex-activation derivative was unexpectedly activated by US. Through a combination of experiments and computation, we find that PMBs likely exert compressive force onto the copolymerized mechanophores rather than the typical elongational forces solvated chain fragments experience in flow. We thereby underscore the mechanochemical properties of the PMB platform and its versatility for accelerated mechanochemical transformations with a perspective on biomedical applications.